Facile microwave assisted synthesis of vastly edge exposed 1T/2H-MoS2 with enhanced activity for hydrogen evolution catalysis. Issue 8 (8th February 2019) - Lee, Young Bum; Kim, Seong K.; Ji, Seulgi; Song, Wooseok; Chung, Hee-Suk; Choi, Moon Kang; Lee, Minbaek; Myung, Sung; Lim, Jongsun; An, Ki-Seok; Lee, Sun Sook
Abstract : One-step microwave-assisted solvothermal synthesis of a 1T–2H MoS2 heterostructure with excellent stability and electrocatalytic performance of 1T-MoS2 as a hydrogen evolution catalyst. Abstract : Energy technologies of the near future will heavily rely on electrochemical systems; hence, the importance of research on electrocatalytically active materials can never be emphasized enough. For hydrogen evolution, precious metal catalysts ( e.g. platinum) are the acclaimed performers, but recently, two-dimensional transition metal dichalcogenides (TMDs) have been receiving immense interest due to their noteworthy catalytic activity and earth-abundance. In particular, molybdenum disulfide (MoS2 ) in its metallic 1T-phase is known to exhibit outstanding performance; thus, utilizing 1T-MoS2 is of high interest. Here, MoS2 is synthesized via a microwave-assisted solvothermal method (MoS2 -MW). Remarkably, the MoS2 -MW film revealed randomly oriented flake-like grains; thus, highly active edge-sites are vastly exposed to the surface. Moreover, investigations of the film exposed the highly stable structural hybrid of the 1T- and 2H-phases, which remarkably exhibits electrocatalytic attributes of pure 1T-MoS2 with superb catalytic activity. The method allows synthesis of MoS2 -MW over morphologically complex conducting substrates to increase both the number and catalytic activity of active sites for hydrogen evolution.